2020
DOI: 10.1111/jre.12824
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal inflammation triggers a site‐specific and wide radius of calcium metabolic effects on alveolar bone

Abstract: Background and Objective There is a close relationship between inflammation and bone remodeling in the periodontium. However, previous studies have not delineated the alterations in calcium (Ca) metabolism during periodontitis progression. The aim of this current investigation was to examine Ca dynamics in alveolar bone of rats during progression of ligature‐induced periodontal inflammation by using 45Ca, which is an index of hard tissue neogenesis. Material and Methods To induce periodontitis, the maxillary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In our previous study using a ligature‐induced periodontitis rat model, we observed increased inflammatory cell infiltration and decreased bone density after 7 days of ligation compared with the control group before ligation 24,37,38 . Spolidorio et al 22 removed the ligature on rat molars 7 days after placement and reported significant recovery of periodontal tissue 8 days later.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our previous study using a ligature‐induced periodontitis rat model, we observed increased inflammatory cell infiltration and decreased bone density after 7 days of ligation compared with the control group before ligation 24,37,38 . Spolidorio et al 22 removed the ligature on rat molars 7 days after placement and reported significant recovery of periodontal tissue 8 days later.…”
Section: Discussionmentioning
confidence: 81%
“…The mean of these three points was used as the representative measurement for each mouse (Figure 2A). In addition, the bone volume fraction (BV/TV) and bone mineral density (BMD) of the alveolar bone were measured within a region of interest (ROI) normalized to the following anatomic indices 23,24 : horizontal section, 300 μm in vertical diameter from 150 μm lateral to the root apex from the CEJ of the second molar; sagittal section, 1,000 μm in proximal diameter from the proximal surface of the third molar; and anterior section, 800 μm in buccal diameter from the palatal root bone wall of the second molar. The total volume of the ROI was 300 × 1000 × 800 μm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Micro-CT analysis of the protective effect of DhHP-6 rats on alveolar bone resorption. To evaluate the effect of DhHP-6 on alveolar bone resorption in rats with periodontitis, we used micro-CT scanning to compare alveolar bone loss and bone structure parameters of the left maxillary first molar of each group of rats [ 33 ]. A 3D reconstruction of the left maxillary of the rats revealed that alveolar bone resorption was obvious in the periodontitis group and the low-dose DhHP-6 group.…”
Section: Resultsmentioning
confidence: 99%
“…Both oral microbiome alterations and physical stimuli by ligation involve the induction of periodontal tissue inflammation 38,39 . In this model, significant inflammation is well‐established at 7 days after ligature placement, 40–42 and the ligation‐induced periodontal tissue destruction reaches an approximate plateau after 14 days 20 . This experimental model can be also used to observe periodontal tissue healing after ligature removal because tissue attachment recovers with the disappearance of inflammation after ligature removal 24 .…”
Section: Discussionmentioning
confidence: 99%